New Access Routes to Privileged and Chiral Ligands for Transition‐Metal Catalyzed Hydrogen Autotransfer (Borrowing Hydrogen), Dehydrogenative Condensation, and Alkene Isomerization Reactions. Issue 12 (23rd November 2021) - Koller, Sebastian; Klein, Philippe; Reinhardt, Katja; Ochmann, Lukas; Seitz, Antonia; Jandl, Christian; Pöthig, Alexander; Hintermann, Lukas
Abstract: A group of transition‐metal catalyzed hydrogen moving reactions, encompassing hydrogen autotransfer (HAT; also called borrowing hydrogen, BH), dehydrogenative condensation (DHC) and alkene isomerization, displays high atom economy and relies on widely available starting materials. Such reactions have considerable potential for clean reaction design and application in sustainable synthesis. With the aim to develop and study synthetic applications of the title reactions, we have set up synthetic access routes to a toolbox of structurally varied ligands for and pincer complexes of some transition metals (cobalt, ruthenium, iridium) that are well established for the title reactions. Ligand target structures, for which often improved syntheses have been found, encompass 6, 6'‐dihydroxy‐2, 2'‐bipyridine, 2(3‐hydroxyphenyl)pyridines (as backbones for PCN pincers), 2(6‐methylpyridine‐2‐yl)pyridines (as backbones for PNN pincers) and 2(3‐tolyl)pyridines (as backbones for PCN pincers). To support research towards asymmetric versions of the title reactions, we have prepared asymmetrically modified versions of well‐established catalysts, including chiral, enantiopure versions of Milstein 's PNN‐ruthenium pincer, Kempe 's triazinyl‐diaminophosphanyl PNP‐iridium‐ or ‐cobalt pincers, Huang 's PCN‐iridium pincers, and Grotjahn 's alkene zipper complex. The strategy applied to 'chiral switching ' relied on replacing symmetric dialkylphosphine donor‐groups by dimenthylphosphine or aryl(menthyl)phosphine donor units. The resulting ligands or complexes have been structurally characterized, and the catalytic potential of the catalysts has been established in exploratory model reactions (transfer hydrogenation; diol to lactone dehydrogenative condensation; alkene isomerization). Several model reactions have been designed which will allow to study asymmetric catalytic hydrogen moving reactions . Abstract :